Management’s Perception of Key Performance Indicators for Vietnam Small and Medium Enterprises - Hung, Ta Huy (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
Key Performance Indicators in performance management system was attracted by researchers and practitioners. In order to effective implemented KPIs in SMEs, managers must deeply understand about the KPIs, role of KPIs, implemented KPIs. Based on the quantitative method by doing survey with 162 SEMs, author indicated the current situation of the perception of SMEs manager about the fundamental of KPI, roles of KPIs  and difficulty implemented KPIs in performance management system. Based on the consistent theory about KPIs , author proposed some solution for manager to enhance their knowledge of KPIs.